2016
DOI: 10.1063/1.4941599
|View full text |Cite
|
Sign up to set email alerts
|

A modified PATH algorithm rapidly generates transition states comparable to those found by other well established algorithms

Abstract: PATH rapidly computes a path and a transition state between crystal structures by minimizing the Onsager-Machlup action. It requires input parameters whose range of values can generate different transition-state structures that cannot be uniquely compared with those generated by other methods. We outline modifications to estimate these input parameters to circumvent these difficulties and validate the PATH transition states by showing consistency between transition-states derived by different algorithms for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(86 citation statements)
references
References 42 publications
(71 reference statements)
2
84
0
Order By: Relevance
“…10(a) (Multimedia view)) 30,33,41 . Replica exchange discrete molecular dynamics 71 showed that the conformational transition state for TrpRS catalytic transition is narrowly defined structurally, and that it coincides with a saddle point in the respective conformational free energy landscape 41 (Fig. 10(b)).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…10(a) (Multimedia view)) 30,33,41 . Replica exchange discrete molecular dynamics 71 showed that the conformational transition state for TrpRS catalytic transition is narrowly defined structurally, and that it coincides with a saddle point in the respective conformational free energy landscape 41 (Fig. 10(b)).…”
Section: Resultsmentioning
confidence: 95%
“…Our recent demonstration that the equilibrium for this catalytic domain movement is driven only by the release of pyrophosphate 41 appears to be an additional mechanism ensuring that catalysis is coupled to (subsequent) domain movement, presumably regulated by tRNA binding. Using PPi release to change the overall conformational equilibrium resembles the behavior observed for myosin, for which the power stroke is initiated by orthophosphate release, whereas the release of adenosine-diphosphate happens only as the power stroke proceeds toward the rigor state 77–79 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We are interested in generating plausible paths between different conformations of the virus capsids, such as the “breathing" induced by increase of temperature (Fibriansah et al, 2013), and the changes observed during the maturation of the virus. We will develop new methods to find such plausible paths in very large systems such as viral capsids, where “plausible" refers to a path with minimal frustration, also defined as the Minimum Action Path (MAP) (Olender and Elber, 1996; Eastman et al, 2001; Franklin et al, 2007; Vanden-Eijnden and Heymann, 2008; Zhou et al, 2008; Chandrasekaran et al, 2016). Finally, we plan to study the impact of glycolsylation of the E protein and/or antibody binding on the virus capsids onto their dynamical properties.…”
Section: Discussionmentioning
confidence: 99%
“…First, as neither intermediate construct would have sufficiently increased fitness to be selected, it suggests that the apparently separate evolutionary enhancements must have occurred coordinately, either because one of the two had already begun to function in trans , or because one or the other, or both modules could “grow” by smaller modular additions that did endow enhanced fitness [33]. Second, the modular thermodynamic cycle involving full-length TrpRS, the two distinct intermediates [33], and the Urzyme allowed measurement of a ΔΔG ‡ ~ − 5 kcal/mole coupling energy between the CP1 and anticodon-binding domains in the transition state of the amino acid activation reaction by full-length TrpRS [33], shedding new light on the general problem of intramolecular signaling or allostery [8991]. …”
Section: Evidence For Bi-directional Coding Ancestry: Molecular Pmentioning
confidence: 99%